Mark‐resight methodology for estimating key deer abundance assisted by citizen scientists. (8th June 2022) - Silvy, Nova J.; Lopez, Roel R.; Lopez, Cristian N.; Breen, Timothy; Lopez, Angelica; Montalvo, Andrea E.; Parker, Israel D.; Powell, Brian
Abstract: Florida Key deer ( Odocoileus virginianus clavium ) are an endangered subspecies of white‐tailed deer endemic to the Lower Florida Keys. The New World screwworm ( Cochliomyia hominivorax ) infestation in July 2016 and Hurricane Irma on 10 September 2017 both caused the Key deer population to decline. Our objective was to estimate current Key deer population abundance using traditional distance sampling and a mark‐resight methodology applicable for citizen scientist participation. For mark‐resight efforts, deer were marked with hand sprayers using water‐based livestock dye on Big Pine (BPK) and No Name keys (NNK). Biologists conducted road surveys between 9–13 March 2020 on BPK and NNK and collected data for mark retention, mark‐resight, and distance calculations concurrently. Our mark‐resight estimate ( n = 748) was nearly 300 deer lower than the traditional distance estimate likely because of distance sampling's sensitivity to increased deer visibility along survey routes. Compared to historic data, our mark‐resight population estimate indicated increased deer abundance compared to post‐Hurricane Irma estimates ( n = 573), but slightly below post‐screwworm outbreak estimates ( n = 860). Based on mark‐retention data, we recommend all resight surveys be completed within 5 days of the first mark placement for the most dependable mark detection. We recommend our mark‐resight method be used in future Key deer surveys as it is simple, efficient, and can be reliably completed with the assistance of volunteers therefore allowing for more regular monitoring. Abstract : Mark‐resight surveys of the endangered Key deer using water‐based livestock dye was a reliable method of estimating population size. We recommend this method be used in future surveys as it can reliably be applied with the assistance of trained volunteers allowing for more regular deer monitoring.